Ectopic solid electrolyte interface modification of lithium metal anodes using chalcogenides

By forming a multi-layer SEI film stack in the anode electrode structure of the lithium-ion battery, the problem of insufficient energy capacity and cycle times of the lithium-ion battery is solved, and more efficient electrochemical performance and lower internal resistance are achieved.

CN119742321APending Publication Date: 2025-04-01APPLIED MATERIALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411770844.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-09
Filing Date
2018-10-02
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing lithium-ion batteries lack sufficient energy capacity and cycle times in applications, and have high internal resistance, which affects the performance of energy storage devices.

Method used

An anode electrode structure is adopted, including forming a lithium metal film on the copper current collector and forming a multi-layer solid electrolyte interface (SEI) film stack on it, specifically including a chalcogenide film, a lithium oxide film, a lithium carbonate film, etc.

Benefits of technology

By modifying the anode electrode structure, the growth of lithium dendrites is suppressed, the circulation performance of lithium metal is improved, the internal resistance is reduced, and the capacity and number of cycles of the energy storage device are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742321A_ABST
    Figure CN119742321A_ABST
Patent Text Reader

Abstract

Implementations described herein generally relate to metal electrodes, and more particularly to lithium-containing anodes, high performance electrochemical devices, such as secondary batteries, including the foregoing lithium-containing electrodes, and methods of making the same. In one implementation, an anode electrode structure is provided. The anode electrode structure includes a current collector comprising copper. The anode electrode structure further includes a lithium metal film formed on the current collector. The anode electrode structure further includes a solid electrolyte interface (SEI) membrane stack formed on the lithium metal membrane. The SEI film stack includes a chalcogenide film formed on the lithium metal film. In one implementation, the SEI film stack further includes a lithium oxide film formed on the chalcogenide film. In one implementation, the SEI film stack further includes a lithium carbonate film formed on the lithium oxide film.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention application is a divisional application of the invention patent application with application number 201880071709.7, application date October 2, 2018, and name “Ex situ solid electrolyte interface modification of lithium metal anode using chalcogenides”. Background Art

[0002] field

[0003] Implementations described herein relate generally to metal electrodes, and more particularly to lithium-containing anodes, high-performance electrochemical devices such as secondary batteries including the aforementioned lithium-containing electrodes, and methods of making the same.

[0004] Related technical description

[0005] Rechargeable electrochemical storage systems are becoming increasingly important in many areas of daily life. High-capacity energy storage devices (such as lithium-ion (Li-ion) batteries and capacitors) are used in more and more applications, including portable electronic devices, medical, transportation, grid-connected large-scale energy storage, renewable energy storage, and uninterruptible power supplies (UPS). In each of these applications, the charge / discharge time and capacity of the energy storage device are key parameters. In addition, the size, weight and / or cost of such energy storage devices are also key parameters. In addition, low internal resistance is necessary for high performance. The lower the resistance, the fewer restrictions the energy storage device encounters when delivering electrical energy. For example, in the case of a battery, the internal resistance affects performance by reducing the total amount of useful energy stored by the battery and the battery's ability to deliver high currents.

[0006] Lithium-ion batteries are considered the most likely to achieve the capacities and cycles sought. However, lithium-ion batteries as currently constructed generally lack the energy capacity and charge / discharge cycle numbers for these growing applications.

[0007] Therefore, what is needed in the art is a faster charging, higher capacity energy storage device with improved cycling and that can be manufactured more cost effectively.What is also needed is a component for an energy storage device that reduces the internal resistance of the storage device. Summary of the invention

[0008] The implementations described herein generally relate to metal electrodes, and more specifically to lithium-containing anodes, high-performance electrochemical devices such as secondary batteries including the aforementioned lithium-containing electrodes, and methods for manufacturing the same. In one implementation, an anode electrode structure is provided. The anode electrode structure includes a current collector including copper. In one implementation, the anode structure includes a copper film. The anode electrode structure further includes a lithium metal film formed on the current collector. The anode electrode structure further includes a solid electrolyte interface (SEI) film stack formed on the lithium metal film. The SEI film stack includes a chalcogenide film formed on the lithium metal film. In one implementation, the SEI film stack further includes a lithium oxide film formed on the chalcogenide film. In one implementation, the SEI film stack further includes a lithium carbonate film formed on the lithium oxide film. In another implementation, the SEI film stack further includes lithium fluoride formed on the chalcogenide film.

[0009] In another implementation, an anode electrode structure is provided. The anode electrode structure includes a current collector including copper. The anode electrode structure further includes a lithium metal film formed on the current collector. The anode electrode structure further includes a solid electrolyte interface (SEI) film stack formed on the lithium metal film. The SEI film stack includes a lithium oxide film, a lithium carbonate film formed on the lithium oxide film, and a chalcogenide film formed on the lithium carbonate film. In an implementation, the SEI film stack further includes a lithium nitride film formed between the lithium metal film and the lithium oxide film.

[0010] In another implementation, a method is provided. The method includes forming a lithium metal film on a current collector, wherein the current collector includes copper. The method further includes forming an SEI film stack on the lithium metal film. Forming the SEI film stack includes forming a chalcogenide film on the lithium metal film, wherein the chalcogenide film is selected from the group consisting of: bismuth chalcogenide, copper chalcogenide, and a combination of the above. In one implementation, the SEI film stack further includes at least one of a lithium fluoride (LiF) film, a lithium carbonate (Li2CO3) film, a lithium oxide film, a lithium nitride (Li3N) film, and a combination of the above. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The above briefly summarizes the manner in which the above-described features of the present disclosure can be understood in detail, as well as a more specific description of implementations, which can be obtained by reference to implementations, some of which are illustrated in the accompanying drawings. However, it should be noted that the drawings illustrate only typical implementations of the present disclosure and should not be considered as limiting the scope of the present disclosure, as the present disclosure may admit of other equally effective implementations.

[0012] Figure 1 illustrates a schematic cross-sectional view of one implementation of an energy storage device incorporating an electrode structure having a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0013] Figure 2 illustrates a cross-sectional view of one implementation of a double-sided anode electrode structure with a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0014] Figure 3 illustrates a cross-sectional view of another implementation of a double-sided anode electrode structure with a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0015] Figure 4 illustrates a cross-sectional view of another implementation of a double-sided anode electrode structure with a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0016] Figure 5 illustrates a cross-sectional view of another implementation of a double-sided anode electrode structure with a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0017] Figure 6 illustrates a cross-sectional view of another implementation of a double-sided anode electrode structure with a formed solid electrolyte interphase (SEI) film stack according to implementations described herein;

[0018] Figure 7 illustrates a process flow diagram of one implementation of a method for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein;

[0019] Figure 8 illustrates a process flow diagram of another implementation of a method for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein;

[0020] Fig. 9 illustrates a process flow diagram of another implementation of a method for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein;

[0021] Fig.10 illustrates a process flow diagram of another implementation of a method for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein;

[0022] Fig.11 illustrates a schematic diagram of an integrated processing tool for forming an anode electrode structure according to implementations described herein;

[0023] Figure 12A to Fig.12D is plotted at 0.25 mA / cm 2 The curve of the battery voltage change versus time of a symmetrical lithium battery (1 hour cycle) at a current density of;

[0024] FIG. 13A to FIG. 13B is a graph of an impedance spectrum of a Li / Li symmetric cell using a chalcogenide modified interface according to implementations described herein;

[0025] Fig.14 is a graph depicting a comparison of a lithium control sample to a chalcogenide modified interface according to implementations described herein;

[0026] Figure 15A to Fig. 15B is an SEM image of lithium of a control cell and a cell having a chalcogenide-modified interface according to implementations described herein;

[0027] FIG. 16A to FIG. 16B is a graph depicting discharge capacity versus cycle number for a bare lithium metal anode and an interface-protected lithium metal anode modified with a chalcogenide according to implementations described herein;

[0028] Fig.17 is a graph depicting cell voltage versus capacity at different discharge rates (0.1C to 5C) for an interface-protected lithium metal anode modified with a chalcogenide according to implementations described herein;

[0029] Fig.18 is a graph depicting the corresponding discharge capacity change versus C rate for an interface-protected lithium metal anode modified with a chalcogenide according to implementations described herein;

[0030] Fig.19 is a graph comparing the percentages of discharge capacity retention at different discharge rates; and

[0031] Fig. 20 is a graph of charge rate capacity change versus C-rate for a comparative control sample to an interface-protected lithium metal anode modified with a chalcogenide according to implementations described herein.

[0032] To facilitate understanding, identical reference numerals have been used, where possible, to designate identical elements that are common to the figures. It is contemplated that elements and features of one implementation may be beneficially incorporated in other implementations without further description. DETAILED DESCRIPTION

[0033] The following disclosure describes a lithium-containing electrode, a high-performance electrochemical device such as a secondary battery including the aforementioned lithium-containing electrode, and a method for manufacturing the same. Figures 1 to 20 Certain details are set forth in order to provide a thorough understanding of various implementations of the present disclosure. Other details describing well-known structures and systems generally associated with electrochemical cells and secondary batteries are not set forth in the following disclosure to avoid unnecessarily obscuring the description of various implementations.

[0034] Many of the details, dimensions, angles, and other features shown in the drawings are merely illustrative of specific implementations. Therefore, other implementations may have other details, components, dimensions, angles, and features without departing from the spirit or scope of the present disclosure. In addition, other implementations of the present disclosure may be practiced without some of the details described below.

[0035] The implementations described herein will be described below with reference to a roll-to-roll coating system, such as Roll-to-roll coating system, Roll-to-roll coating system, Roll-to-roll web coating systems, all of which are available from Applied Materials, Inc. of Santa Clara, California. Other tools capable of performing high rate deposition processes may also be adapted to benefit from the implementations described herein. In addition, any system that implements the deposition processes described herein may be advantageously used. The device descriptions described herein are exemplary and should not be understood or interpreted as limitations on the scope of the implementations described herein. It should also be understood that, although described as a roll-to-roll process, the implementations described herein may also be performed on discrete substrates.

[0036] The development of rechargeable lithium metal batteries is considered a promising technology that can achieve high energy density systems for energy storage. However, current lithium metal batteries are plagued by dendrite growth, which hinders the practical application of lithium metal batteries in portable electronic devices and electric vehicles. During several charge / discharge cycles, microscopic fibers of lithium, called dendrites, form on the surface of lithium metal and spread until they contact the other electrode. Passing current through these dendrites may short-circuit the battery. One of the most challenging aspects of achieving lithium metal battery technology is the development of a stable and efficient solid electrolyte interphase (SEI). A stable and efficient SEI provides an effective strategy to inhibit dendrite growth and thereby achieve improved cycling.

[0037] The current SEI film is typically formed in situ in the battery formation cycle process, which is generally performed immediately after battery manufacturing. During the battery formation cycle process, when an appropriate potential is established on the anode and a specific organic solvent is used as an electrolyte, the organic solvent is decomposed and forms a SEI film during the first charge. For typical liquid electrolytes and at lower current densities, mossy lithium deposits have been reported, and lithium growth is attributed to "bottom growth". At higher current densities, the concentration gradient in the electrolyte leads to "tip growth", and this tip growth leads to a short circuit in the battery. Depending on the organic solvent used, the SEI film formed on the anode is typically a mixture of lithium oxide, lithium fluoride, and semi-carbonate. Initially, the SEI film is electrically insulating, but has sufficient conductivity for lithium ions. SEI can prevent the electrolyte from decomposing after the second charge. SEI can be considered as a three-layer system with two key interfaces. In conventional electrochemical studies, SEI is often referred to as a double layer. The simplest form of SEI is that the anode coated with SEI will go through three stages when charging. These three stages include electron transfer (M) between the anode (M) and the SEI 0 —ne→M n+ M / SEI ); Cation migration from the anode-SEI interface to the SEI-electrolyte (E) interface (M n+ M / SEI →M n+ SEI / E ); and cation transfer from SEI to electrolyte at SEI / electrolyte interface (E(solv)+M n+ SEI / E →M n+ E(solv)).

[0038] The power density and charging speed of the battery depend on how quickly the anode can release and obtain charge. This in turn depends on how quickly the anode can exchange lithium ions with the electrolyte through the SEI. The lithium ion exchange at the SEI is a multi-stage process, and like most multi-stage processes, the speed of the entire process depends on the slowest stage. Studies have shown that anion migration is the bottleneck of most systems. In addition, it is believed that the diffusion properties of the solvent determine the speed of migration between the anode-SEI interface and the SEI-electrolyte (E) interface. Therefore, the best solvents have almost no mass in order to maximize the diffusion rate.

[0039] Although the specific properties and reactions occurring at the SEI are not well understood, it is believed that these properties and reactions have a profound effect on the cycle and capacity of the anode electrode structure. It is also believed that the SEI thickens during cycling, thereby slowing down the diffusion from the electrode / SEI interface to the SEI / electrolyte. For example, at elevated temperatures, alkyl carbonates in the electrolyte decompose into insoluble Li2CO3, which may increase the thickness of the SEI film, block the pores of the SEI film, and restrict the access of lithium ions to the anode. SEI growth may also occur through gas evolution at the cathode and particle migration toward the anode. This in turn increases impedance and reduces capacity. In addition, the randomness of the metallic lithium embedded in the anode during embedding causes dendrite formation. Over time, dendrites pierce the separator, resulting in a short circuit, which in turn results in heating, fire, and / or explosion.

[0040] The implementation of the present disclosure involves constructing a stable and effective SEI film in situ. The SEI film is formed in the energy storage device during the manufacture of the energy storage device. Compared with the existing lithium-based anodes that rely on in-situ SEI films, this new and efficient SEI film is believed to be able to inhibit lithium dendrite growth and thereby achieve excellent lithium metal cycling performance.

[0041] Figure 1 A cross-sectional view of one implementation of an energy storage device 100 in combination with an anode electrode structure having a formed SEI film stack 140 according to the implementations described herein is illustrated. In some implementations, the energy storage device 100 is a rechargeable battery cell. In some implementations, the energy storage device 100 is combined with other battery cells to form a rechargeable battery. The energy storage device 100 has a cathode current collector 110, a cathode film 120, a separator film 130, a SEI film stack 140, an anode film 150, and an anode current collector 160. Figure 1 Note that although the current collector and separator are shown extending beyond the stack, the current collector does not have to extend beyond the stack, and the portion extending beyond the stack can be used as a tab. The SEI film stack 140 can have more than one layer combined with at least one of lithium carbonate (Li2CO3), lithium oxide (Li2O), lithium nitride (Li3N), and lithium fluoride (LiF), such as a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film).

[0042] In one implementation, the portion of the SEI film stack 140 is formed by exposing the lithium film to a SF6 gas treatment to form the LiF and Li2S portions of the SEI film stack 140 on the surface of the lithium film. The SF6 gas can be activated to thermally react with the exposed lithium surface, or the SF6 gas can be plasma activated. The thickness of the SEI film stack 140 can be controlled by modifying the SF6 gas exposure time and temperature.

[0043] The current collectors 110 and 160 on the cathode film 120 and the anode film 150, respectively, may be the same or different electronic conductors. Examples of metals that the current collectors 110 and 160 may include include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), tin (Sn), silicon (Si), manganese (Mn), magnesium (Mg), alloys of the above, and combinations thereof. In one implementation, at least one of the current collectors 110 and 160 is perforated. In addition, the current collector may have any form factor (e.g., metal foil, sheet or plate), shape, and micro / macro structure. In one implementation, at least one of the current collectors 110 and 160 includes a polyethylene terephthalate ("PET") film coated with a metallic material. In one implementation, the anode current collector 160 is a PET film coated with copper. In another implementation, the anode current collector 160 is a multi-metal layer on PET. The multi-metal layer may be a combination of copper, chromium, nickel, and the like. In one implementation, the anode current collector 160 is a multilayer structure including a copper-nickel cladding material. In one implementation, the multilayer structure includes a first layer of nickel or chromium, a second layer of copper formed on the first layer, and a third layer including nickel, chromium, or both formed on the second layer. In one implementation, the anode current collector 160 is nickel-plated copper. In addition, the current collector can have any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. Generally, in prismatic batteries, the tabs are formed of the same material as the current collector and can be formed during the manufacture of the stack or added later. All components except the current collectors 110 and 160 contain lithium ion electrolytes. In one implementation, the cathode current collector 110 is aluminum. In one implementation, the cathode current collector 110 has a thickness from about 0.5 μm to about 20 μm (e.g., from about 1 μm to about 10 μm; from about 5 μm to about 10 μm). In one implementation, the anode current collector 160 is copper. In one implementation, the anode current collector 160 has a thickness from about 0.5 μm to about 20 μm (eg, from about 1 μm to about 10 μm; from about 2 μm to about 8 μm; from about 5 μm to about 10 μm).

[0044] The anode film 150 or anode can be any material compatible with the cathode film 120 or cathode. The anode film 150 can have an energy capacity greater than or equal to 372mAh / g, preferably ≥700mAh / g, and most preferably ≥1000mAh / g. The anode film 150 can be made of lithium metal, lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy), or a mixture of lithium metal and / or lithium alloy with the following materials: such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, the above oxides, or a combination thereof. The anode film 150 typically includes an intercalation compound containing lithium or an insertion compound containing lithium. In some implementations in which the anode film 150 includes lithium metal, the method described herein can be used to deposit lithium metal. The anode film can be formed by extrusion, physical or chemical thin film technology, such as sputtering, electron beam evaporation, chemical vapor deposition (CVD), three-dimensional printing, lithium powder deposition, etc. In one embodiment, the anode film 150 has a thickness from about 0.5 μm to about 20 μm (e.g., from about 1 μm to about 10 μm; from about 5 μm to about 10 μm). In one embodiment, the anode film 150 is a lithium metal or lithium metal alloy film. The SEI film stack 140 is formed ectopically on the anode film 150. The SEI film stack 140 is electrically insulating, but has sufficient conductivity for lithium ions. In one embodiment, the SEI film stack 140 is a non-porous film. In another embodiment, the SEI film stack 140 is a porous film. In one embodiment, the SEI film stack 140 has a plurality of nanopores, the nanopore size being set to have an average pore size or diameter of less than about 10 nanometers (e.g., from about 1 nanometer to about 10 nanometers; from about 3 nanometers to about 5 nanometers). In another embodiment, the SEI film stack 140 has a plurality of nanopores, the nanopore size being set to have an average pore size or diameter of less than about 5 nanometers. In one implementation, the SEI film stack 140 has a plurality of nanopores having diameters ranging from about 1 nanometer to about 20 nanometers (eg, from about 2 nanometers to about 15 nanometers; or from about 5 nanometers to about 10 nanometers).

[0045] The SEI film stack 140 can be a coating or a discrete layer having a thickness in the range of 1 nm to 200 nm (e.g., in the range of 5 nm to 200 nm; in the range of 10 nm to 50 nm). Without being bound by theory, it is believed that SEI films greater than 200 nm can increase resistance within a rechargeable battery.

[0046] Examples of materials that may be included in the SEI film stack 140 include, but are not limited to, a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film) or a composite chalcogenide film optionally combined with at least one of a lithium carbonate (Li2CO3) film, a lithium oxide (Li2O) film, a lithium nitride film (Li3N), and a lithium halide film (e.g., LiF, LiCl, LiBr, or LiI). In one implementation, the SEI film stack 140 includes a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film). Without being bound by theory, it is believed that the SEI film stack 140 can absorb a lithium conductive electrolyte to form a gel during device fabrication, which is beneficial for forming a good solid electrolyte interface (SEI) and also helps reduce resistance. Suitable methods for depositing a portion of the SEI film stack 140 directly on the lithium metal film include, but are not limited to: physical vapor deposition (PVD), such as evaporation or sputtering; slot die process; thin film transfer process; or three-dimensional lithium printing process. Portions of the SEI film stack may be formed by plasma treatment of previously deposited layers (e.g., oxygen plasma treatment of exposed lithium surfaces to form a lithium oxide film).

[0047] The cathode film 120 or cathode may be any material that is compatible with the anode and may include an intercalation compound, an insertion compound, or an electrochemically active polymer. Suitable intercalation materials include, for example, lithium-containing metal oxides, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, V6O 13 and V2O5. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, and polythiophene. The cathode film 120 or cathode may be made of a layered oxide such as lithium cobalt oxide, an olivine such as lithium iron phosphate, or a spinel such as lithium manganese oxide. Exemplary lithium-containing oxides may be layered, such as lithium cobalt oxide (LiCoO2), or may be mixed metal oxides such as LiNi x Co 1-2x MnO2, LiNiMnCoO2 (“NMC”), LiNi 0.5 Mn 1.5 O4、Li(Ni 0.8 Co 0.15 Al 0.05 )O2, LiMn2O4 and doped lithium-rich layered materials, where x is zero or a non-zero number. Exemplary phosphates can be olivine iron (LiFePO4) and its variants (such as LiFe (1-x) Mg xPO4, wherein x is between 0 and 1), LiMoPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiVOPO4, LiMP2O7 or LiFe 1.5 P2O7, where x is zero or a non-zero number. Exemplary fluorophosphates may be LiVPO4F, LiAlPO4F, Li5V(PO4)2F2, Li5Cr(PO4)2F2, Li2CoPO4F, or Li2NiPO4F. Exemplary silicates may be Li2FeSiO4, Li2MnSiO4, or Li2VOSiO4. An exemplary non-lithium compound is Na5V2(PO4)2F3. The cathode film 120 may be formed by extrusion, physical or chemical thin film techniques such as sputtering, electron beam evaporation, chemical vapor deposition (CVD), and the like. In one implementation, the cathode film 120 has a thickness from about 10 μm to about 100 μm (e.g., from about 30 μm to about 80 μm; from about 40 μm to about 60 μm). In one implementation, the cathode film 120 is a LiCoO2 film. In another implementation, the cathode film 120 is an NMC film.

[0048] The separator film 130 includes a porous (e.g., microporous) polymer substrate material (e.g., separator film) capable of conducting ions with pores. In some embodiments, the porous polymer substrate itself does not need to be ionically conductive, but once filled with an electrolyte (liquid, gel, solid, combination, etc.), the combination of the porous substrate and the electrolyte is ionically conductive. In one embodiment, the porous polymer substrate is a multilayer polymer substrate. In one embodiment, the pores are micropores. In some embodiments, the porous polymer substrate is composed of any commercially available polymer microporous membrane (e.g., monolayer or multilayer), such as Polypore (Celgard Inc., Charlotte, North Carolina), Toray Tonen (battery separator film (BSF)), SK Energy (SK Energy) (lithium-ion battery separator film (LiBS), Evonik Industries ( Ceramic diaphragm), Asahi Kasei (Hipore TM Polyolefin flat film diaphragm), DuPont In some implementations, the porous polymer substrate has a porosity in the range of 20% to 80% (e.g., in the range of 28% to 60%). In some implementations, the porous polymer substrate has an average pore size in the range of 0.02 microns to 5 microns (e.g., 0.08 microns to 2 microns). In some implementations, the porous polymer substrate has a Gurley value in the range of 15 seconds to 150 seconds (Gurley value refers to the time it takes for 10cc of air to pass through a square inch of membrane at 12.2 inches of water). In some implementations, the porous polymer substrate is a polyolefin. Exemplary polyolefins include polypropylene, polyethylene, or a combination of the above.

[0049] In some implementations of the energy storage device of the present disclosure, for example, the lithium metal film of the anode electrode contains lithium, and lithium manganese oxide (LiMnO4) or lithium cobalt oxide (LiCoO2) is at the cathode electrode, but in some implementations, the anode electrode may also include a lithium absorbing material such as silicon, tin, etc. The energy storage device, even if shown as a planar structure, may be formed into a cylinder by rolling a stack of layers; in addition, implementations of the present disclosure also contemplate other battery configurations (e.g., prismatic batteries, button batteries).

[0050] The electrolyte injected into the battery components 120, 130, 140 and 150 can be composed of liquid / gel or solid polymer, and can be different. In some embodiments, the electrolyte mainly includes a salt and a medium (for example, in a liquid electrolyte, the medium can be called a solvent; in a gel electrolyte, the medium can be a polymer matrix). The salt can be a lithium salt. The lithium salt can include, for example, LiPF6, LiAsF6, LiCF3SO3, LiN(CF3SO3)3, LiBF6 and LiClO4, bistrifluoromethylsulfonyl imide lithium (for example, LiTFSI), BETTE electrolyte (commercially available from 3M Company (3M Corp. of Minneapolis, MN) in Minnesota) and combinations thereof. The solvent may include, for example, ethylene carbonate (EC), propylene carbonate (PC), EC / PC, 2-MeTHF (2-methyltetrahydrofuran) / EC / PC, EC / DMC (dimethyl carbonate), EC / DME (dimethyl ethane), EC / DEC (diethyl carbonate), EC / EMC (ethyl methyl carbonate), EC / EMC / DMC / DEC, EC / EMC / DMC / DEC / PE, PC / DME, and DME / PC. The polymer matrix may include, for example, PVDF (polyvinylidene fluoride), PVDF:THF (PVDF:tetrahydrofuran), PVDF:CTFE (PVDF:chlorotrifluoroethylene), PAN (polyacrylonitrile), and PEO (polyethylene oxide).

[0051] Figure 2 A cross-sectional view of one implementation of a double-sided anode electrode structure 200 with a formed solid electrolyte interphase (SEI) film stack 240a, 240b (collectively 240) according to implementations described herein is illustrated. The SEI film stack 240a, 240b may replace Figure 1 The depicted SEI film stack 140 is used. Each SEI film stack 240a, 240b includes a chalcogenide film 210a, 210b (collectively referred to as 210) formed on each anode film 150a, 150b, respectively. The chalcogenide film is selected from the group consisting of: copper chalcogenide (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe), bismuth chalcogenide (e.g., Bi2Te3, Bi2Se3) and combinations thereof.

[0052] Figure 3 A cross-sectional view of another implementation of a double-sided anode electrode structure 300 having a formed solid electrolyte interphase (SEI) film stack 340a, 340b (collectively 340) according to implementations described herein is illustrated. The SEI film stack 340a, 340b may replace Figure 1 The depicted SEI film stack 140 is used. Each SEI film stack 340a, 340b includes a chalcogenide film 210a, 210b (collectively referred to as 210) formed on each anode film 150a, 150b, respectively. The chalcogenide film is selected from the group consisting of: copper chalcogenide (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe), bismuth chalcogenide (e.g., Bi2Te3, Bi2Se3) and combinations thereof. Each SEI film stack 340a, 340b also includes a Li2O film 310a, 310b (collectively referred to as 310) formed on the chalcogenide film 210a, 210b (collectively referred to as 210). Each SEI film stack 340a, 340b also includes a Li2CO3 film 320a, 320b (collectively referred to as 320) formed on the Li2O film 310a, 310b (collectively referred to as 310).

[0053] Figure 4 A cross-sectional view of another implementation of a double-sided anode electrode structure 400 having a formed solid electrolyte interphase (SEI) film stack 440a, 440b (collectively 440) according to implementations described herein is illustrated. The SEI film stack 440a, 440b may replace Figure 1The depicted SEI film stack 140 is used. Each SEI film stack 440a, 440b includes a Li2O film 310a, 310b (collectively referred to as 310) formed on each anode film 150a, 150b, respectively. Each SEI film stack 440a, 440b also includes a Li2CO3 film 320a, 320b (collectively referred to as 320) formed on the Li2O film 310a, 310b (collectively referred to as 310). Each SEI film stack 540a, 540b also includes a chalcogenide film 210a, 210b (collectively referred to as 210) formed on the Li2CO3 film 320a, 320b (collectively referred to as 310).

[0054] Figure 5 A cross-sectional view of another implementation of a double-sided anode electrode structure 500 with a formed solid electrolyte interphase (SEI) film stack 540a, 540b (collectively 540) according to implementations described herein is illustrated. The SEI film stack 540a, 540b may replace Figure 1 The depicted SEI film stack 140 is used. Each SEI film stack 540a, 540b includes a lithium nitride (Li3N) film 510a, 510b (collectively referred to as 510) formed on each anode film 150a, 150b, respectively. Each SEI film stack 540a, 540b also includes a Li2O film 310a, 310b (collectively referred to as 310) formed on each lithium nitride film 510a, 510b, respectively. Each SEI film stack 540a, 540b also includes a Li2CO3 film 320a, 320b (collectively referred to as 320) formed on the Li2O film 310a, 310b (collectively referred to as 310). Each SEI film stack 540a, 540b also includes a chalcogenide film 210a, 210b (collectively referred to as 210) formed on the Li2CO3 film 320a, 320b (collectively referred to as 310).

[0055] Figure 6 A cross-sectional view of one implementation of a double-sided anode electrode structure 600 with a formed solid electrolyte interphase (SEI) film stack 640a, 640b (collectively 640) according to implementations described herein is illustrated. The SEI film stack 640a, 640b may replace Figure 1The depicted SEI film stack 140 is used. Each SEI film stack 640a, 640b includes a chalcogenide film 210a, 210b (collectively referred to as 210) formed on each anode film 150a, 150b, respectively. The chalcogenide film is selected from the group consisting of: copper chalcogenide (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe), bismuth chalcogenide (e.g., Bi2Te3, Bi2Se3) and combinations thereof. Each SEI film stack 640a, 640b also includes a lithium halide film 610a, 610b (collectively referred to as 610) formed on the chalcogenide film 210a, 210b (collectively referred to as 210). In one implementation, the lithium halide film is selected from LiF, LiCl, LiBr and LiI.

[0056] exist Figures 2 to 6 Note that although the anode current collector 160 is shown extending beyond the stack, the anode current collector 160 does not have to extend beyond the stack, and the portion extending beyond the stack may serve as a tab. Figures 2 to 6 The depicted anode structure is depicted as a double-sided electrode structure, but it should be understood that Figures 2 to 6 The described implementation is also applicable to single-sided electrode structures.

[0057] Figure 7 A process flow diagram of one implementation of a method 700 for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein is illustrated. In one implementation, the anode electrode structure is Figure 2 The depicted double-sided anode electrode structure 200. In another implementation, the anode electrode structure is Figure 3 The depicted double-sided anode electrode structure 300. At operation 710, a substrate is provided. In one implementation, the substrate is Fig.11 Continuous material sheet 1150 is shown. In one implementation, the substrate is an anode current collector 160. Examples of metals that the substrate may include include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, cladding materials, alloys of the above, and combinations thereof. In one implementation, the substrate is a copper material. In one implementation, the substrate is perforated. In addition, the substrate can have any form factor (e.g., metal foil, sheet or plate), shape, and micro / macro structure.

[0058] In some implementations, the substrate is exposed to a pretreatment process that includes at least one of a plasma treatment or a corona discharge process to remove organic material from an exposed surface of the current collector. The pretreatment process is performed prior to film deposition on the substrate.

[0059] At operation 720, a lithium metal film is formed on the substrate. In one implementation, the lithium metal film is the anode film 150, and the substrate is the anode current collector 160. In one implementation, the lithium metal film is formed on the copper current collector. In some implementations, if the anode film already exists on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film can be directly formed on the substrate. Any suitable lithium metal film deposition process for depositing lithium metal film can be used to deposit the lithium metal film. The deposition of lithium metal film can be carried out by a PVD process, such as evaporation, sputtering process, slot die process, transfer process or three-dimensional lithium printing process. The chamber for depositing lithium metal film may include: a PVD system, such as an electron beam evaporator, a thermal evaporator or a sputtering system); a thin film transfer system (including a large area pattern printing system, such as a gravure printing system); or a slot die deposition system. In one implementation, the anode film 150 has a thickness of 100 microns or less (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; from or about 50 μm to about 100 μm).

[0060] At operation 730, a SEI film stack is formed on the lithium metal film. The SEI film stack includes a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film) and optionally a lithium carbonate (Li2CO3) film and a lithium oxide (Li2O) film. In one implementation, similar to Figure 2 The SEI film stack 240 depicted includes only chalcogenide films (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 films). In another implementation, similar to Figure 3 As depicted, the SEI film stack 340 includes only a chalcogenide film (e.g., a CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film), a lithium oxide film formed on the chalcogenide film, and a lithium carbonate film formed on the lithium oxide film.

[0061] At operation 740, a chalcogenide film is formed on the lithium metal film. In one implementation, the chalcogenide film is a Bi2Te3 film. In one implementation, the chalcogenide film is Figures 2 to 6Chalcogenide film 210 is depicted. In one implementation, the chalcogenide film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; from about 100 nm to about 150 nm; from about 10 nm to about 80 nm; or from about 30 nanometers to about 60 nanometers). In one implementation, the chalcogenide film is deposited using a PVD process with an RF power source coupled to a target. The target is typically composed of the material of the chalcogenide film. In one implementation, the target is a bismuth telluride alloy target. In one implementation, the bismuth telluride alloy target contains from about 5 atomic % to about 95 atomic % bismuth and from about 5 atomic % to about 95 atomic % tellurium. The plasma can be generated by a non-reactive gas such as argon (Ar), krypton (Kr), nitrogen, etc. For example, the plasma may be generated by argon gas having a flow rate in the range of about 30 standard cubic centimeters (sccm) to about 200 sccm, such as about 100 sccm to about 150 sccm. RF power may be applied to the target at a power level in the range of from about 50 W to about 4,000 W, for example, in the range of from about 1000 W to about 3000 W, such as about 2000 W. The deposition chamber may be pressurized from about 0.1 mTorr to about 500 mTorr. The deposition chamber may be pressurized from about 0.1 mTorr to about 100 mTorr, for example, from about 10 mTorr to about 30 mTorr, such as 25 mTorr. The substrate may be electrically "floating" and not biased. The deposition process of operation 740 may be performed at a deposition temperature from about 50° C. to about 400° C., for example, from about 100° C. to about 200° C., such as about 120° C.

[0062] In another implementation, a plasma may be generated using a DC power source coupled to a bismuth telluride alloy target. The substrate may be electrically "floating" and not biased. In this implementation, the plasma may be generated by argon gas having a flow rate in the range of about 30 standard cubic centimeters (sccm) to about 200 sccm, such as about 100 sccm to about 150 sccm. DC power may be applied to the target at a power level in the range of from about 50 W to about 5,000 W, from about 1000 W to about 3000 W, for example, between about 1000 W to about 2000 W, such as about 2000 W. The deposition chamber may be pressurized from about 0.1 mTorr to about 500 mTorr. The deposition chamber may be pressurized from about 0.1 mTorr to about 500 mTorr. The deposition chamber may be pressurized from about 0.1 mTorr to about 100 mTorr, for example, from about 10 mTorr to about 30 mTorr, such as 25 mTorr. The substrate may be electrically "floating" and unbiased. The deposition process of operation 740 may be performed at a deposition temperature from about 50° C. to about 400° C., for example, from about 100° C. to about 200° C., such as about 120° C.

[0063] Optionally, at operation 750, a lithium oxide (Li2O) film is formed on the chalcogenide film. In one implementation, the lithium oxide film is Figures 2 to 6 Depicted lithium oxide film 310. In one implementation, the lithium oxide film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 4000 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nanometers). In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film on the chalcogenide film and exposing the lithium metal film to a plasma oxidation process to oxidize the lithium metal film. In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film via PVD in an oxygen-containing atmosphere. In one implementation, a portion of the lithium metal film deposited during operation 720 remains exposed during operation 740 after the chalcogenide film is deposited. The exposed portion of the lithium metal film is then exposed to a plasma oxidation process to form the lithium oxide film.

[0064] Optionally, at operation 760, a lithium carbonate (Li2CO3) film is formed on the lithium oxide film. In one implementation, the lithium carbonate film is Figures 3 to 5Depicted lithium carbonate film 320. In one implementation, the lithium carbonate film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nanometers). In one implementation, the lithium carbonate film is formed by depositing an additional lithium metal film on the lithium oxide film and exposing the lithium metal film to a plasma oxidation process (e.g., a gas treatment using at least one of O2 and CO2) to oxidize the lithium metal film. In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film via PVD in an oxygen-containing atmosphere (e.g., an atmosphere containing at least one of O2 and CO2). In one implementation, a portion of the lithium oxide film deposited during operation 750 is exposed to a plasma oxidation process to form the lithium carbonate film.

[0065] Figure 8 A process flow diagram of another implementation of a method 800 for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein is illustrated. In one implementation, the anode electrode structure is Figure 4 The depicted double-sided anode electrode structure 400. In another implementation, the anode electrode structure is Figure 5 The depicted double-sided anode electrode structure 500. At operation 810, a substrate is provided. In one implementation, the substrate is Fig.11 Continuous material sheet 1150 is shown. In one implementation, the substrate is an anode current collector 160. Examples of metals that the substrate may include include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, cladding materials, alloys of the above, and combinations thereof. In one implementation, the substrate is a copper material. In one implementation, the substrate is perforated. In addition, the substrate can have any form factor (e.g., metal foil, sheet or plate), shape, and micro / macro structure.

[0066] In some implementations, the substrate is exposed to a pretreatment process that includes at least one of a plasma treatment or a corona discharge process to remove organic material from an exposed surface of the current collector. The pretreatment process is performed prior to film deposition on the substrate.

[0067] At operation 820, a lithium metal film is formed on the substrate. In one implementation, the lithium metal film is the anode film 150, and the substrate is the anode current collector 160. In one implementation, the lithium metal film is formed on the copper current collector. In some implementations, if the anode film already exists on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film can be directly formed on the substrate. Any suitable lithium metal film deposition process for depositing lithium metal film can be used to deposit the lithium metal film. The deposition of lithium metal film can be carried out by a PVD process, such as evaporation, sputtering process, slot die process, transfer process or three-dimensional lithium printing process. The chamber for depositing lithium metal film may include: a PVD system, such as an electron beam evaporator, a thermal evaporator or a sputtering system; a thin film transfer system (including a large area pattern printing system, such as a gravure printing system); or a slot die deposition system. In one implementation, the anode film 150 has a thickness of 100 microns or less (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; from or about 50 μm to about 100 μm).

[0068] At operation 830, a SEI film stack is formed on the lithium metal film. The SEI film stack includes a lithium oxide (Li2O) film, a lithium carbonate (Li2CO3) film, a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film), and an optional lithium nitride (Li3N) film (see Figure 5 ). In one implementation, similar to Figure 5 The SEI film stack 540 depicted includes a lithium nitride (Li3N) film formed on a lithium metal film, a lithium oxide (Li2O) film formed on the lithium nitride film, a lithium carbonate (Li2CO3) film formed on the lithium oxide film, and a chalcogenide film (e.g., Bi2Te3 film) formed on the lithium carbonate film. In another implementation, similar to Figure 4 The SEI film stack 440 depicted includes a lithium oxide (Li2O) film formed on a lithium metal film, a lithium carbonate (Li2CO3) film formed on the lithium oxide film, and a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film) formed on the lithium carbonate film.

[0069] Optionally, at operation 840, a lithium nitride (Li3N) film is formed on the lithium metal film. In one implementation, the lithium nitride film is Figure 5Depicted lithium nitride film 510. In one implementation, the lithium nitride film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 1 nm to about 50 nanometers). In one implementation, the lithium nitride film is formed by depositing an additional lithium metal film on the lithium metal film and exposing the lithium metal film to a plasma nitridation process to form the lithium nitride film. In one implementation, the lithium nitride film is formed by depositing the additional lithium metal film via PVD in a nitrogen-containing atmosphere.

[0070] At operation 850, a lithium oxide (Li2O) film is formed. If a lithium nitride film is present, a lithium oxide film is formed on the lithium nitride film. If lithium nitride is not present, a lithium oxide film is formed on the lithium metal film. In one implementation, the lithium oxide film is Figures 4 to 5 Depicted lithium oxide film 310. In one implementation, the lithium oxide film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 4000 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nanometers). In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film on the lithium nitride film and exposing the lithium metal film to a plasma oxidation process to oxidize the lithium metal film. In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film via PVD in an oxygen-containing atmosphere. In one implementation, the lithium nitride film is exposed to a plasma oxidation process to form the lithium oxide film. In one implementation in which there is no lithium nitride film, the lithium metal film deposited during operation 820 is exposed to a plasma oxidation process to form the lithium oxide film.

[0071] At operation 860, a lithium carbonate (Li2CO3) film is formed on the lithium oxide film. In one implementation, the lithium carbonate film is Figures 4 to 5 Depicted lithium carbonate film 320. In one implementation, the lithium carbonate film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nanometers). In one implementation, the lithium carbonate film is formed by depositing an additional lithium metal film on the lithium oxide film and exposing the lithium metal film to a plasma oxidation process (e.g., a gas treatment using at least one of O2 and CO2) to oxidize the lithium metal film. In one implementation, the lithium oxide film is formed by depositing an additional lithium metal film via PVD in an oxygen-containing atmosphere (e.g., an atmosphere containing at least one of O2 and CO2). In one implementation, a portion of the lithium oxide film deposited during operation 750 is exposed to a plasma oxidation process to form the lithium carbonate film.

[0072] At operation 870, a chalcogenide film is formed on the lithium carbonate film. In one implementation, the chalcogenide film is a Bi2Te3 film. In one implementation, the chalcogenide film is Figures 4 to 5 The chalcogenide film 210 is depicted. In one implementation, the chalcogenide film is deposited using the process conditions described in operation 740. In one implementation, the chalcogenide film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; from about 100 nm to about 150 nm; from about 10 nm to about 80 nm; or from about 30 nanometers to about 60 nanometers). Any suitable deposition process may be used to form the chalcogenide film. In one implementation, the chalcogenide film is deposited using the process described for operation 740.

[0073] Fig. 9 A process flow diagram of another implementation of a method 900 for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein is illustrated. In one implementation, the anode electrode structure is Figure 6 The depicted double-sided anode electrode structure 600. At operation 910, a substrate is provided. In one implementation, the substrate is Fig.11 Continuous material sheet 1150 is shown. In one implementation, the substrate is an anode current collector 160. Examples of metals that the substrate may include include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, cladding materials, alloys of the above, and combinations thereof. In one implementation, the substrate is a copper material. In one implementation, the substrate is perforated. In addition, the substrate can have any form factor (e.g., metal foil, sheet or plate), shape, and micro / macro structure.

[0074] In some implementations, the substrate is exposed to a pretreatment process that includes at least one of a plasma treatment or a corona discharge process to remove organic material from an exposed surface of the current collector. The pretreatment process is performed prior to film deposition on the substrate.

[0075] At operation 920, a lithium metal film is formed on the substrate. In one implementation, the lithium metal film is the anode film 150, and the substrate is the anode current collector 160. In one implementation, the lithium metal film is formed on the copper current collector. In some implementations, if the anode film already exists on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film can be directly formed on the substrate. Any suitable lithium metal film deposition process for depositing lithium metal film can be used to deposit the lithium metal film. The deposition of lithium metal film can be carried out by a PVD process, such as evaporation, sputtering process, slot die process, transfer process or three-dimensional lithium printing process. The chamber for depositing lithium metal film may include: a PVD system, such as an electron beam evaporator, a thermal evaporator or a sputtering system; a thin film transfer system (including a large area pattern printing system, such as a gravure printing system); or a slot die deposition system. In one implementation, the anode film 150 has a thickness of 100 microns or less (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; from or about 50 μm to about 100 μm).

[0076] At operation 930, a SEI film stack is formed on the lithium metal film. Figure 6 The SEI film stack 640 depicted includes a chalcogenide film (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film), and a lithium fluoride (LiF) film formed on the chalcogenide film.

[0077] At operation 940, a chalcogenide film is formed on the lithium carbonate film. In one implementation, the chalcogenide film is a Bi2Te3 film. In one implementation, the chalcogenide film is Figures 4 to 5 The chalcogenide film 210 is depicted. In one implementation, the chalcogenide film is deposited using the process conditions described in operation 740. In one implementation, the chalcogenide film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; from about 100 nm to about 150 nm; from about 10 nm to about 80 nm; or from about 30 nanometers to about 60 nanometers). Any suitable deposition process may be used to form the chalcogenide film. In one implementation, the chalcogenide film is deposited using the process described for operation 740.

[0078] At operation 950, a lithium halide film is formed on the chalcogenide film. In one implementation, the lithium halide film is Figure 6Depicted lithium halide film 610. In one implementation, the lithium halide film is deposited on the chalcogenide film by physical vapor deposition (PVD), special atomic layer deposition (ALD), slot die process, thin film transfer process, or three-dimensional lithium printing process, physical vapor deposition such as evaporation or sputtering. In one implementation, PVD is a method for depositing lithium fluoride film. In one implementation, the lithium halide film is selected from LiF, LiCl, LiBr and LiI. In one implementation, the lithium halide film is a lithium fluoride film. In one implementation, the lithium halide film is deposited using a thermal evaporation process. In one implementation, the lithium fluoride film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nm).

[0079] Fig.10 A process flow diagram of another implementation of a method 1000 for forming an anode electrode structure having a solid electrolyte interphase (SEI) film stack according to an overview of implementations described herein is illustrated. In one implementation, the anode electrode structure is Figure 6 The depicted double-sided anode electrode structure 600. At operation 1010, a substrate is provided. In one implementation, the substrate is Fig.11 Continuous material sheet 1150 is shown. In one implementation, the substrate is an anode current collector 160. Examples of metals that the substrate may include include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, cladding materials, alloys of the above, and combinations thereof. In one implementation, the substrate is a copper material. In one implementation, the substrate is perforated. In addition, the substrate can have any form factor (e.g., metal foil, sheet or plate), shape, and micro / macro structure.

[0080] In some implementations, the substrate is exposed to a pretreatment process that includes at least one of a plasma treatment or a corona discharge process to remove organic material from an exposed surface of the current collector. The pretreatment process is performed prior to film deposition on the substrate.

[0081] At operation 1020, a lithium metal film is formed on a substrate. In one implementation, the lithium metal film is an anode film 150, and the substrate is an anode current collector 160. In one implementation, a lithium metal film is formed on a copper current collector. In some implementations, if an anode film already exists on the substrate, a lithium metal film is formed on the anode film. If there is no anode film 150, a lithium metal film can be formed directly on the substrate. Any suitable lithium metal film deposition process for depositing a lithium metal film can be used to deposit a lithium metal film. The deposition of the lithium metal film can be performed by a PVD process, such as evaporation, a sputtering process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing a lithium metal film may include: a PVD system, such as an electron beam evaporator, a thermal evaporator, or a sputtering system; a thin film transfer system (including a large area pattern printing system, such as a gravure printing system); or a slot die deposition system. In one implementation, the anode film 150 has a thickness of 100 microns or less (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; from or about 50 μm to about 100 μm).

[0082] At operation 1030, a SEI film stack is formed on the lithium metal film. The SEI film stack includes a composite film of lithium halide and chalcogenide. In one implementation, the SEI film stack also includes at least one of a lithium fluoride (LiF) film, a lithium carbonate (Li2CO3) film, a lithium oxide film, a lithium nitride (Li3N) film, a chalcogenide film, and a combination thereof. The composite film may be a composite film including a chalcogenide material (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 film) and a lithium halide material (e.g., lithium fluoride).

[0083] At operation 1040, a lithium halide and chalcogenide composite film is formed on the underlying film (e.g., lithium metal film). In one implementation, the lithium halide and chalcogenide composite film is a LiF and Bi2Te3 composite film. In one implementation, the lithium halide and chalcogenide composite film is Figures 4 to 5Chalcogenide film 210 is depicted. In one implementation, the lithium halide and chalcogenide composite film is deposited using the process conditions described in operation 740, operation 940, or a combination of the processes of operations 740 and 940. In one implementation, the lithium halide and chalcogenide composite film has a thickness of 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; from about 100 nm to about 150 nm; from about 10 nm to about 80 nm; or from about 30 nanometers to about 60 nanometers). The lithium halide and chalcogenide composite film may be formed using any suitable deposition process. In one implementation, the lithium halide and chalcogenide composite film is deposited by physical vapor deposition (PVD) (such as evaporation or sputtering), special atomic layer deposition (ALD), slot die process, thin film transfer process, three-dimensional lithium printing process, or a combination of the above. In one implementation, PVD is the method used to deposit the lithium fluoride film.

[0084] Fig.11 FIG. 1 is a schematic diagram of a flexible substrate coating apparatus 1100 for forming an anode electrode structure according to an implementation described herein. The flexible substrate coating apparatus 1100 may be manufactured by Applied Materials, Inc. The apparatus is adapted to manufacture a lithium anode device according to the implementations described herein. According to a typical implementation, the flexible substrate coating apparatus 1100 can be used to manufacture a lithium anode, and in particular, a SEI film stack for a lithium anode. The flexible substrate coating apparatus 1100 is configured as a roll-to-roll system, which includes an unwinding module 1102, a processing module 1104, and a winding module 1106. In certain implementations, the processing module 1104 includes a plurality of processing modules or chambers 1110, 1120, 1130, and 1140 arranged in sequence, each processing module or chamber being configured to perform a processing operation on a continuous material sheet 1150 or a material coil. In one implementation, as Fig.11 As depicted, process chambers 1110-1140 are radially disposed about coating drum 1155. Arrangements other than radial are contemplated. For example, in another implementation, the process chambers may be positioned in a linear configuration.

[0085] In one implementation, the processing chambers 1110 to 1140 are independent modular processing chambers, wherein each modular processing chamber is structurally separated from the other modular processing chambers. Therefore, each independent modular processing chamber can be independently arranged, rearranged, replaced or maintained without affecting each other. Although four processing chambers 1110 to 1140 are shown, it should be understood that any number of processing chambers can be included in the flexible substrate coating apparatus 1100.

[0086] The processing chambers 1110 to 1140 may include any suitable structure, configuration, arrangement and / or component that enables the flexible substrate coating device 1100 to deposit a lithium anode device according to the implementation of the present disclosure. For example, but not limited to, the processing chamber may include a suitable deposition system, which includes a coating source, a power supply, a separate pressure control, a deposition control system, and a temperature control. According to a typical implementation, the chamber is provided with a separate gas supply. The chambers are typically separated from each other to provide good gas separation. The flexible substrate coating device 1100 according to the implementation described herein is not limited in the number of deposition chambers. For example, but not limited to, the flexible substrate coating device 1100 may include 3, 6 or 12 processing chambers.

[0087] The processing chambers 1110 to 1140 typically include one or more deposition units 1112, 1122, 1132 and 1142. Generally, one or more deposition units as described herein can be selected from the group of the following items: CVD source, PECVD source and PVD source. One or more deposition units may include an evaporation source, a sputtering source, such as a magnetron sputtering source, a DC sputtering source, an AC sputtering source, a pulsed sputtering source, and radio frequency (RF) sputtering or medium frequency (MF) sputtering can be provided. For example, MF sputtering with a frequency in the range of 5kHz to 100kHz, for example, in the range of 30kHz to 50kHz can be provided. One or more deposition units may include an evaporation source. In one implementation, the evaporation source is a thermal evaporation source or an electron beam evaporation. In one implementation, the evaporation source is a lithium (Li) source. In addition, the evaporation source may also be an alloy of two or more metals. The material to be deposited (e.g., lithium) may be provided in a crucible. Lithium may be evaporated, for example, by thermal evaporation technology or by electron beam evaporation technology.

[0088] In some implementations, any one of the processing chambers 1110 to 1140 of the flexible substrate coating apparatus 1100 can be configured to perform deposition by sputtering such as magnetron sputtering. As used herein, "magnetron sputtering" refers to sputtering performed using a magnet assembly, that is, sputtering performed using a unit capable of generating a magnetic field. Typically, such a magnet assembly includes a permanent magnet. This permanent magnet is typically arranged in a rotatable target, or coupled to a planar target, in such a manner that free electrons are trapped in a magnetic field generated below the surface of the rotatable target. Such a magnet assembly can also be arranged to be coupled to a planar cathode.

[0089] Magnetron sputtering can also be achieved with a dual magnetron cathode, such as, but not limited to, the TwinMag TMCathode assembly. In some implementations, the cathodes in the processing chambers can be interchangeable. Thus, a modular design of the apparatus is provided, which facilitates optimization of the apparatus for a specific manufacturing process. In some implementations, the number of cathodes in the chamber for sputtering deposition is selected to optimize the best productivity of the flexible substrate coating apparatus 1100.

[0090] In some implementations, one or some of the processing chambers 1110 to 1140 can be configured to perform sputtering without a magnetron assembly. In some implementations, one or some of the chambers can be configured to perform deposition by other methods, such as but not limited to chemical vapor deposition, atomic laser deposition, or pulsed laser deposition. In some implementations, one or some of the chambers can be configured to perform a plasma treatment process, such as a plasma oxidation or plasma nitridation process.

[0091] In some implementations, the processing chambers 1110 to 1140 are configured to process both sides of the continuous material sheet 1150. Although the flexible substrate coating apparatus 1100 is configured to process a horizontally oriented continuous material sheet 1150, the flexible substrate coating apparatus 1100 can be configured to process substrates positioned in different orientations, for example, the continuous material sheet 1150 can be oriented vertically. In some implementations, the continuous material sheet 1150 is a flexible conductive substrate. In some implementations, the continuous material sheet 1150 includes a conductive substrate with one or more layers formed thereon. In some implementations, the conductive substrate is a copper substrate.

[0092] In certain implementations, the flexible substrate coating apparatus 1100 includes a transfer mechanism 1152. The transfer mechanism 1152 may include any transfer mechanism capable of moving a continuous material sheet 1150 through the processing areas of the processing chambers 1110 to 1140. The transfer mechanism 1152 may include a common transport architecture. The common transport architecture may include a reel-to-reel system having a common receiving reel 1154 positioned in the winding module 1106, a coating drum 1155 positioned in the processing module 1104, and a feed reel 1156 positioned in the unwinding module 1102. The receiving reel 1154, the coating drum 1155, and the feed reel 1156 may be heated individually. The receiving reel 1154, the coating drum 1155, and the feed reel 1156 may be heated individually using an internal heat source or an external heat source positioned within each reel. The common transport architecture may also include one or more auxiliary transfer reels 1153a, 1153b positioned between the receiving reel 1154, the coating drum 1155, and the feeding reel 1156. Although the flexible substrate coating apparatus 1100 is depicted as having a single processing area, in some implementations, each discrete processing chamber 1110 to 1140 may advantageously have a separate or discrete processing area. For implementations with discrete processing areas, modules, or chambers, the common transport architecture may be a reel-to-reel system in which each chamber or processing area has a separate receiving reel and feeding reel and one or more optional intermediate transfer reels positioned between the receiving reel and the feeding reel.

[0093] The flexible substrate coating apparatus 1100 may include a feed reel 1156 and a receiving reel 1154 for moving a continuous material sheet 1150 through different processing chambers 1110 to 1140. In one implementation, the first processing chamber 1110 and the second processing chamber 1120 are each configured to deposit a portion of a lithium metal film. The third processing chamber 1130 is configured to deposit a chalcogenide film. The fourth processing chamber 1140 is configured to deposit a lithium oxide or lithium fluoride film above the chalcogenide film. In another implementation in which the continuous material sheet 1150 is a polymer material, the processing chamber 1110 is configured to deposit a copper film on the polymer material. The second processing chamber 1120 and the third processing chamber 1130 are each configured to deposit a portion of a lithium metal film. The fourth processing chamber 1140 is configured to deposit a chalcogenide film. In some implementations, the completed negative electrode will not be collected on a receiving reel 1154 as shown, but can be directly integrated with a separator and positive electrode, etc. to form a battery cell.

[0094] In one implementation, the processing chambers 1110 to 1120 are configured to deposit a lithium metal film on the continuous material sheet 1150. Any suitable lithium deposition process for depositing a lithium metal film can be used to deposit the lithium metal film. The deposition of the lithium metal film can be performed by a PVD process, such as evaporation, a slot die process, a transfer process, a lamination process, or a three-dimensional lithium printing process. The chamber for depositing the lithium metal film may include: a PVD system, such as an electron beam evaporator; a film transfer system (including a large area pattern printing system, such as a gravure printing system); a lamination system; or a slot die deposition system.

[0095] In one implementation, the third processing chamber 1130 is configured to deposit a chalcogenide film on the lithium metal film. The chalcogenide film can be deposited using a PVD sputtering technique as described herein. In one implementation, the fourth processing chamber 1140 is configured to form a lithium oxide film or a lithium fluoride film on the chalcogenide film. Any suitable lithium deposition process for depositing a lithium metal film can be used to deposit a lithium metal film. The deposition of the lithium metal film can be performed by a PVD process, such as evaporation, a slot die process, a transfer process, a lamination process, or a three-dimensional lithium printing process. In one implementation, the fourth processing chamber 1140 is an evaporation chamber or a PVD chamber, which is configured to deposit a lithium fluoride film or a lithium oxide film above a continuous material sheet 1150. In one implementation, the evaporation chamber has a processing area, which is shown as including an evaporation source that can be placed in a crucible, which can be, for example, a thermal evaporator or an electron beam evaporator (cold) in a vacuum environment.

[0096] In operation, a continuous material sheet 1150 is unwound from a feed reel 1156, as indicated by the direction of substrate movement shown by arrow 1108. The continuous material sheet 1150 may be guided via one or more auxiliary transfer reels 1153a, 1153b. The continuous material sheet 1150 may also be guided by one or more substrate guidance control units (not shown) that control the correct advancement of the flexible substrate, for example by finely adjusting the orientation of the flexible substrate.

[0097] After unwinding from the feed reel 1156 and traveling over the auxiliary transport reel 1153a, the continuous material sheet 1150 is then moved through a deposition area provided at the coating drum 1155 and corresponding to the positions of the deposition units 1112, 1122, 1132 and 1142. During operation, the coating drum 1155 rotates about the axis 1151 so that the flexible substrate moves in the direction of the arrow 1108.

[0098] Example:

[0099] The following non-limiting examples are provided to further illustrate the implementations described herein. However, the examples are neither intended to be all-inclusive nor intended to limit the scope of the implementations described herein.

[0100] The lithium samples were cut into 1.0 cm 2 The wafer is polished with a stainless steel brush in an argon glove box. After this, lithium is pressed with polypropylene sandwiched in between to obtain a fine metallic luster foil. A lithium foil with a thickness of about 160 μm is placed on a stainless steel gasket and transferred to a PVD deposition chamber using a transfer container. The target in the PVD deposition chamber is n-type, with a composition of 38.6% Bi, 55.1% Te. Argon is filled into the PVD deposition chamber, and a continuous argon flow of about 150 sccm is established. The deposition time is about 90 seconds. A process pressure of about 25 mTorr is established in the PVD deposition chamber. A deposition temperature of about 120 degrees Celsius is established in the PVD deposition chamber. A deposition power of 2 kW is used (for For example, a spacing of about 57 mm was established between the target and the lithium sample. After the Bi2Te3 deposition process was completed, the sample was transferred to an argon glove box for further study. The thickness of the deposited Bi2Te3 film varied between about 50 nm and 200 nm. Coin cells including lithium and Bi2Te3 films were assembled and tested.

[0101] Figure 12A to Fig.12D is plotted at 0.25 mA / cm 2 Figure 2. Cell voltage variation versus time for a symmetric lithium battery (1 hour cycle) at a current density of 1.5 Å. Li / Li symmetric cell studies are extremely suitable for investigating the reversibility of the Li anode. Fig.11 The figure shows the cell arrangement of the control cell. The control cell is a Li||Li symmetric cell with bare lithium foil as electrode, while FIG. 12B to FIG. 12D The figure shows a Bi2Te3 protected cell using a lithium foil with a few nanometers of Bi2Te3 on top as the electrode (Li|Bi2Te3||Bi2Te3|Li). A standard electrolyte containing 1M LiPF6 in EC / DEC solvent was used (volume ratio = 1:1). The symmetric cell with the standard electrolyte was assembled into a 2032 coin cell and operated at 0.250 mA / cm 2 and 3mA / cm 2 As the cycle progresses, lithium plating and stripping continuously change the surface of lithium. From Figures 12A and Fig. 12B It is noted that the fresh protected cells exhibit higher impedance due to the insulating nature of Bi2Te3, however, after formation cycles, the impedance decreases and outperforms the control cell.

[0102] FIG. 13A to FIG. 13B13 is a graph of the impedance spectra of a Li / Li symmetric cell using a Bi2Te3 modified interface and an unmodified lithium control. The impedance spectra of the Li / / Li symmetric cell using a Bi2Te3 modified interface are shown as trace 1310, while the unmodified lithium control is shown as trace 1320. After cycling for 300 hours with the Bi2Te3 modified interface as shown in trace 1340, the interface resistance as shown in trace 1330 decreases dramatically.

[0103] Fig.14 is depicted at 0.250 mA / cm as shown at points 1410a to 1410d. 2 and 3 mA / cm as shown at points 1420a to 1420d 2 Graph comparing the voltage drop of the control sample to the interface modified by Bi2Te3 as shown in Examples 1 to 3 after polarization for 100 hours at a current density of . In contrast, the Bi2Te3 protected battery exhibits stable cycling capability for up to 400 hours at the same current density and a low degree of polarization (-150 mV) ( Fig. 12B and Fig. 12C ). Therefore, the excellent cycling ability of the protected battery means homogeneous lithium deposition and less lithium and electrolyte consumption in the battery. The stable cycling ability proves the effectiveness of Bi2Te3 in improving and limiting lithium dendrite formation and enhancing reversibility.

[0104] FIG. 15A is a SEM image of a lithium control cell. Fig. 15B is a SEM image of a Bi2Te3 protected battery. The morphology of the lithium metal electrode surface from galvanostatic cycling measurements was analyzed by scanning electron microscopy. Fig. 15B The lithium surface after cycling for 50 charge / discharge cycles in 1M LiPF6 (EC:DEC 2% FEC) is shown. The lithium electrode forms needle-like nanostructures in contact with the control lithium metal, as shown in FIG15A , while the lithium surface forms a dense and uniform electrodeposition in contact with the Bi2Te3 film, as shown in FIG15A . Fig. 15B These results demonstrate that both the voltage instability and improved stability observed in FIG12A originate from the interface modification of Bi2Te3.

[0105] FIG. 16A to FIG. 16B is a graph depicting the discharge capacity versus cycle number for bare Li metal anode and Li metal anode protected with Bi2Te3. Li / LiCoO2 CR2032 coin cells with Bi2Te3 modified Li served as a proof-of-concept platform for testing the efficacy of the anode passivation process described herein. All-metal cells were fabricated using Li metal as anode and commercially available lithium cobalt oxide as cathode in combination with 1M LiPF6 (EC:DEC 2% FEC) electrolyte. Fig.16AIt was observed that cells containing 50nm to 100nm Bi2Te3 on the lithium surface provided 33mA / cm 2 The improved capacity retention for at least 30 charge-discharge cycles at a high current density of 1.5 mAh / cm2 was achieved. Protecting the lithium metal with Bi2Te3 not only prevents this self-discharge during the remaining period before starting electrochemical cycling, but also prevents capacity loss during the first 10 cycles, where the capacity of the battery using the Bi2Te3-protected anode increased from about 3.5 mAh / cm2 to about 1.5 mAh / cm2. 2 decreased by a negligible amount, such as Fig. 16B After 30 cycles, the battery with the bare lithium metal anode loses its initial capacity more significantly, while the battery with the protected lithium metal anode has little loss.

[0106] To evaluate the rate capability of the control and Bi2Te3 coated samples, the electrodes were subjected to charge-discharge cycles with different currents and the discharge capacity values ​​were Fig.17 and Fig.18 Shown in. Fig.19 It is a graph comparing the percentage of discharge capacity retention at different discharge rates. Fig. 20 is a graph comparing the change in charge rate capacity versus C rate. It should be seen that for the comparative example, the discharge capacity retention of the material remains very stable and gives a 95% capacity retention at a 1C discharge rate. To further illustrate, a comparison of the charge capacity retention is plotted. In this example, lithium is deposited on top of the modified interface. This shows that the Bi2Te3 coating of the electrode has a positive impact on the retention compared to the control example, with a capacity retention of 80% at C / 10, C / 5, C / 2, 1C and 2C rates. This further illustrates the advantages of coating Bi2Te3 on Li metal.

[0107] In general, some implementations of the present disclosure provide methods for constructing stable and effective SEI films including chalcogenide materials and devices incorporating the SEI films. The SEI film is formed in an energy storage device during its manufacture (e.g., ex situ). The inventors have discovered that including a chalcogenide material in the SEI film helps inhibit lithium dendrite growth. Without being bound by theory, it is believed that inhibiting lithium dendrite growth helps achieve excellent lithium metal cycling performance relative to current lithium-based anodes that rely on an in situ SEI film that is formed during the first charge of the energy storage device.

[0108] When introducing elements of the present disclosure or exemplary aspects or implementations of the present disclosure, the articles “a,” “an,” “the,” and “said” are intended to mean that there are one or more of the elements.

[0109] The terms “comprising,” “including,” and “having” are intended to be inclusive and mean that there may be additional elements other than the listed elements.

[0110] While the foregoing is directed to implementations of the present disclosure, other and further implementations of the disclosure may be devised without departing from the basic scope thereof, and the scope of the disclosure is determined by the claims which follow.

Claims

1. A method comprising: forming a lithium metal film on a current collector, wherein the current collector comprises a copper film; and Forming a solid electrolyte interface (SEI) film stack on the lithium metal film, comprising: A chalcogenide film is formed on the lithium metal film, wherein the chalcogenide film is selected from a bismuth telluride film, a bismuth selenide film, or a combination thereof.

2. The method of claim 1, wherein the SEI film stack further comprises a lithium fluoride (LiF) film, a lithium carbonate (Li2CO3) film, a lithium oxide film, a lithium nitride (Li3N) film, or a combination thereof.

3. The method of claim 2, wherein the lithium metal film has a thickness of about 1 micron to about 20 microns. The method of claim 3 , wherein the chalcogenide film is Bi 2 Te 3 .

5. The method of claim 1, wherein the current collector comprises: a first film containing nickel or chromium; the copper film formed on the first nickel- or chromium-containing film and having a thickness of about 50 nanometers to about 500 nanometers; and A second nickel or chromium containing film is formed on the copper film and has a thickness of about 20 nanometers to about 50 nanometers.

6. The method of claim 1, wherein the current collector comprises: Polyethylene terephthalate (PET) polymer substrate; and The copper film is formed on the PET polymer substrate, wherein the copper film is deposited via a physical vapor deposition process. 7 . The method of claim 1 , wherein the current collector including the copper film is exposed to a plasma treatment or a corona discharge process to remove organic materials from an exposed surface of the current collector.

8. An anode electrode structure comprising: a current collector, the current collector comprising a copper film; a lithium metal film formed on the current collector; and A solid electrolyte interface (SEI) film stack, the SEI film stack formed on the lithium metal film, comprising: A chalcogenide film is formed on the lithium metal film, wherein the chalcogenide film is selected from a bismuth telluride film, a bismuth selenide film, or a combination thereof. 9 . The anode electrode structure of claim 8 , wherein the SEI film stack further comprises a lithium fluoride film formed on the chalcogenide film.

10. The anode electrode structure of claim 8, wherein the chalcogenide film is Bi2Te3. 11 . The anode electrode structure of claim 8 , wherein the SEI film stack further comprises a lithium oxide film formed on the chalcogenide film. 12 . The anode electrode structure of claim 11 , wherein the SEI film stack further comprises a lithium carbonate film formed on the lithium oxide film.

13. An anode electrode structure comprising: a current collector, the current collector comprising a copper film; a lithium metal film formed on the current collector; and A solid electrolyte interface (SEI) film stack, the SEI film stack formed on the lithium metal film, comprising: Lithium oxide membrane; a lithium carbonate film, the lithium carbonate film being formed on the lithium oxide film; and A chalcogenide film is formed on the lithium carbonate film, wherein the chalcogenide film is selected from a bismuth telluride film, a bismuth selenide film or a combination thereof. 14 . The anode electrode structure of claim 13 , wherein the SEI film stack further comprises a lithium nitride film formed between the lithium metal film and the lithium oxide film.

15. The anode electrode structure of claim 13, wherein the chalcogenide film is selected from Bi2Te3, Bi2Se3 or a combination thereof.

16. The anode electrode structure of claim 15, wherein the chalcogenide film is Bi2Te3.

17. The anode electrode structure of claim 15, wherein the chalcogenide film has a thickness of about 1 nanometer to about 400 nanometers.

18. The anode electrode structure of claim 17, wherein the lithium metal film has a thickness of about 1 micron to about 20 microns.